Adjuvant Treatment for Pancreatic Cancer - Daoud, Vladimir; Saif, Muhammad Wasif; Goodman, Martin (JOP. Journal of the Pancreas, 2014)
Pancreatic cancer is the fourth leading cause of cancer deaths in both men and women. Surgical resection has been shown to be the only curable treatment available. Unfortunately only 20% of all patients diagnosed with pancreatic cancer are surgical candidates due to the aggressive biology of this disease. There is no clear consensus on what type of adjuvant therapy should be used for patients with pancreatic cancer. Chemoradiation is the favored treatment modality by many in the United States while gemcitabine based chemotherapy is favored in Europe. Both of these approaches have been shown by large prospective, randomized trials to improve disease free intervals and in some studies overall survival. The survival of these patients, even status post resection and adjuvant therapy, remains poor and therefore the need for alternative adjuvant therapies is needed. We will therefore discuss Abstracts #4124, #TPS4162, #4120 and #E15191 in this paper which are relevant to the issues described above. Image: Tufts University Medford campus (Author: Alonso Nichols / Tuft University Photo)